Immunophenotyping of gastritis, gastric ulcer and gastric cancer using a cluster of differentiation (CD) antibody microarray - Alfizah Hanafiah,; Asif Sukri,; Nik Ritza Kosai,; Mohamad Aznan Shuhaili,; Mustafa Mohammed Taher,; Raja Affendi Raja Ali, (Penerbit Universiti Kebangsaan Malaysia, 2023)
One of the factors that contribute to the development of gastric cancer is the host immune response. Extensive immunophenotype of gastric cancer can be identified by using antibody microarray technique that profiles more than 100 cluster of differentiation (CD) antigens in parallel. In this study, we used DotScanTM antibody microarray to profile CD antigen expression in patients with distinct digestive diseases for surface antigen disease-signatures. Patients’ blood samples with gastric disorders and healthy controls were taken and processed for leukocytes isolation using Histopaque density gradient centrifugation. Leukocytes were captured onto DotScanTM slides and cell binding densities were analyzed using DotReaderTM. Different groups of gastric diseases were found to be characterized by differentially expressed distinct CD antigens. Compared to normal healthy controls, 17, two and four highly expressed CD antigens were identified in gastritis, gastric ulcer and gastric cancer patients, respectively. The 17 CD antigens that show differential expression in gastritis were CD15, CD16, CD20, CD23, CD24, CD25, CD28, CD34, CD37, CD77, CD102, CD103, CD122, CD128, CD10, CD183, and CD184. High expression of CD64 and CD69 were found in gastric ulcer, whereas CD52, CD126, CD135, and CD121a were highly expressed in gastric cancer. CD antigens involve in T-cell functions had reduced expression in gastric cancer, while proinflammatory cytokines shows increased expression. These results demonstrate specific immunophenotype of CD antigens in patients with various gastric diseases and identification of differential expressed surface antigens may have clinical significance for diagnostic and therapeutic purposes.